Synthesis, structural and thermal characterizations, dielectric properties and in vitro cytotoxic activities of new 2,2,4,4-tetra(4?- oxy-substituted-chalcone)-6,6-diphenylcyclotriphosphazene derivatives - Koran, Kenan; Tekin, Çiğdem; Biryan, Fatih; Tekin, Suat; Sandal, Süleyman; Görgülü, Ahmet Orhan (My University, 2017)
In this study, we aimed to investigate the relationship between the cytotoxic and dielectric properties of newly synthesized 2,2,4,4-tetra(4?-oxy-substituted-chalcone)- 6,6-diphenylcyclotriphosphazene derivatives (3–10). Firstly, 2,2,4,4-tetrachloro-6,6-diphenyl cyclotriphosphazene (2) was obtained through Friedel Crafts alkylation in the presence of hexachlorocyclotriphosphazene, benzene and triethylamine and anhydrous AlCl3. The compounds 3–10 were synthesized from the reaction of the hydroxychalcone compounds (1a–h) with 2 in the presence of K2CO3 and within the acetone solvent for the first time and their dielectric constant, dielectric loss factor and ac conductivity of compounds 3–10 were examined through the impedance analyzer as a function of frequency. The in vitro cytotoxic activities of compounds 3–10 in five different concentrations (1, 5, 25, 50, and 100 µM) were analyzed by colorimetric MTT assay which is based on reduction of MTT salt by mitochondria of alive cells over the human ovarian cancer (A2780) and human prostate cancer (PC-3 and LNCaP) cell lines. The LogIC50 values of 3–10 were calculated by using a Graphpad prism 6 programs on a computer. The obtained results suggests that the compounds have a powerful cytotoxic activity (especially A2780, p < 0.05).
Yeni 2,2,4,4-tetra(4?- oksi-ssübstitüe-kalkon)-6,6-difenilsiklotrifosfazen türevlerinin, sentezi, yapısal ve termal karakterizasyonu, dielectrik özellikleri ve in vitro sitotoksik aktiviteleri
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Chalcone-cyclotriphosphazene; Cancer cell lines; Dielectric property; Cytotoxic activity; Dielectric constant